Riddah as an Obstacle to Hadhanah in the Perspective of Maqāṣid al-Syarī‘ah: Analysis of East Jakarta PA Decision No.1700/Pdt.G/2010/PAJT - Akbar, Ali; Nelli, Jumni (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The jurists set several conditions for those entitled to custody of children, one of which is being Muslim. Riddah (leaving Islam) is normatively seen as an obstacle to ḥaḍānah because it is feared that it can affect the child's faith and religious education. This article aims to determine the Maqasid Syariah review of the Judge's rejection of the right of Hadanah for apostate mothers as stated in the Religious Court Decision Number PA Jakarta Timur No.1700/Pdt.G/2010/PAJT. This type of research is Normative research with a Statutory approach. Primary data are the East Jakarta Religious Court Decision Number 1700/Pdt.G/2010/PAJT, as well as laws and Islamic legal provisions related to Hadanah and Riddah, while secondary legal materials are obtained from fiqh literature, books, scientific journals, and relevant scientific works. The data collection technique is documentation, and the analysis is qualitative. The results of this article show that case No. /Pdt. G/2010/2010 / PAJT did not grant Hadanah rights to apostate mothers. In this decision, the judge understood Riddah as an obstacle to Hadanah as a consideration in the Hadanah decision. As discussed in the book Kifayatul Akhyar, as a basis for understanding fiqh, it is a requirement that parents who have the obligation to educate and raise children be Muslim, so that the judge's decision rejects the plaintiff's or appellant's petition if the plaintiff or appellant is an apostate. The Panel of Judges has prioritized hifz al-ddin (dhoruriyat) and hifdz an-nafs (care for the soul) to consider the benefit and best interests of the child